GREEN FINANCE: THE PRACTICES OF BANKS AND PERSPECTIVE OF CUSTOMERS - Chopra, Tripti; Kakrecha, Punit (International Journal of Research -GRANTHAALAYAH, 2015)
Green financing is a term which is trending these days. Significant evidence was traced in 2007 when business week reportedly said that a fifteen-fold rise was there in sustainable mutual fund investment. There is a shift from capital formation to energy efficiency in investments. In 1980s and 1990s the focus of investments was mostly on economically viable projects. But this is the era when the focus has been shifted to environmentally viable projects. There are many companies which are following green finance concept so as to sustain in long run. A report on “Measures for ensuring sustained growth of Indian manufacturing sector” or Prime Minister’s group headed by V Krishnamurthy recommended for promotion of clean technologies to achieve the aim of sustainable growth. The major objective of this paper is to study several aspects of green financing with respect to Indian scenario and it would also verify the practicability of green financing in Indian Banking sector. Green financing is now becoming a trending concept in the industry. Besides all the facts, the public is also demanding a company to be environmentally sensitive. Due to this reason many business houses have already started green financing. But this is indeed a crucial time for the companies to cope up with standards and norms of Green financing. Environmental improvements and economic growth should go hand in hand specially in countries like India so as to sustain and develop in long run.